Implementasi Kebijakan Good Governance Pemerintah DKI Jakarta Dalam Menangani Pandemi Covid-19 - Ana Chaerunisyah (CV ODIS, 2021)
This research aims to analyze the policies and efforts taken by the Jakarta government to deal with Covid 19. This research is qualitative research with descriptive methods of analysis and data collection techniques using literature studies. The results showed that the policies and efforts made have not been fully effective in handling Covid 19 in Jakarta. Obstacles in handling stem from community non-compliance and weak coordination of central and local governments.